In vitro activities of Malaysian antidiabetic plant extracts on adipocytes cell - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Darnis, Deny Susanti (IIUM Press, 2011)
Diabetes mellitus is widely known as a metabolic disorder and it is becoming a major public health concern in most developing countries. The majority of type 2 patients are sufficiently insulin-resistant, which is defined as defective insulin signaling and a decreased insulin efficiency to induce glucose transport from the blood into key target cells such as muscle and fat cells (adipocyte) (Khan et aI., 2003). For these patients, more insulin is not necessarily the ideal treatment strategy. A multitude of herbs, spices, and other plant materials have been described for the treatment of diabetes mellitus around the world. To date, the demand for natural products is high and thus, this has increased attention to alternative medicines